Mutational signatures are jointly shaped by DNA damage and repair - Nadezda V. Volkova (Nature Portfolio, 2020)
Recent research has shown that mutational signatures reflective of the history of a cancer can be detected in a cancer genome. Here, using whole genome sequencing of DNA repair deficient and proficient nematodes exposed to genotoxins, the authors show that these mutational signatures reflect both the initial DNA damage that was inflicted and the repair processes that ensue.